Exploring the Intent of Agro-pastoral Entrepreneurs Trained in Agricultural Colleges of Northwest Cameroon - Vitung, Aseh Emmanuel; Anu, Shelacha Sheila (CV. Literasi Indonesia, 2024)
The entrepreneurship intentions of agro-pastoral entrepreneurs and those in training in colleges of agriculture in Cameroon are not well understood. This is due to the paucity of data on their motivations for enrolment in the agricultural entrepreneurship course, their propensity to create agricultural enterprises upon completion of the training, and the difficulties they face in creating their enterprises. A case study of the Regional College of Agriculture, Bambili in the Northwest region of Cameroon was conducted during which, open-ended questionnaires were administered to individuals and focus groups. The data collected were analyzed using the thematic framework. Themes emerged on the various categories of information sought. The study revealed that youths are motivated mainly by perceived opportunities to take agricultural entrepreneurship training. Entrepreneurs have positive intentions to create agricultural enterprises post-training, however, they are constrained by difficult access to land, limited finances, unsupportive laws, and complex bureaucratic procedures for enterprise creation. Government land reforms, the pursuit of the strategy on inclusive financing and the easing of procedures for registration of enterprises will incentivise trained entrepreneurs to create formal agricultural enterprises. Further research in agricultural colleges in other agroecological zones will consolidate the understanding of the intentions of youths who take entrepreneurship training and elicit informed decisions from policymakers.